A hemicyanine complex for the detection of thiol biomolecules by fluorescence. (August 2016) - Nhan, Doan Thanh; Hien, Nguyen Khoa; Van Duc, Hoang; Ai Nhung, Nguyen Thi; Trung, Nguyen Tien; Van, Dang Ung; Shin, Weon Sup; Kim, Jong Seung; Quang, Duong Tuan
Abstract: Herein, we report the design and preparation of a benzothiazolium hemicyanine derivative that exhibits red emission at 585 nm. Its complex with Hg 2+ may be used for selective and sensitive sensing of thiol biomolecules through the reversible visual color and florescence changes they induce in the complex. This complex was used to detect three test thiol biomolecules, and exhibited sensitivity in the order cysteine > glutathione > homocysteine. Furthermore, the complex allowed the detection of cysteine at 0.2 μM, lower than the normal human intracellular cysteine concentration (30–200 μM), and was found to be useable over at least five cycles upon alternate addition of cysteine and Hg 2+ . Graphical abstract: Highlights: A complex of Hg 2+ can be used sense mercapto biomolecules such as cysteine, homocysteine and glutathione. The sensing ability is as follows, cysteine > glutathione > homocysteine. The reaction time for the probe can be completed within several seconds. The probe can detect Cys at the level much lower than the intracellular Cys concentration. The probe can operate at least 5 cycles upon alternate addition of cysteine and Hg 2+ .